The Influence of External Elements on The Human Decision-Making Process - Yohannes Bramanda Ryan Kharisma; Indra Tanureja (Societas Dei: Jurnal Agama dan Masyarakat)
This paper is a critical analysis of two important texts in two cultural traditions, namely the story of “The Fall” in Genesis chapter 3 in the Judeo-Christian tradition and “Sang Durjodana Arsa Ngasoraké Pandawa sarana Prang Dadu” in the Mahabharata epic in the Javanese tradition, Sadjarah Pandawa Korawa, by Raden Tanojo. The analysis process of juxtaposing the two texts will use the characterization method that focuses on the speech and actions performed by the serpent and Sengkuni as a representation of external elements that are capable of influencing human actions. Both are portrayed as intelligent and cunning, and they use their cunning to tempt other characters, Eve and Yudhistira, to sin or mistake. In addition, a text reading of the Book of Genesis can provide a perspective that not everything has to end with war and violence in the Mahabharata. Also, a text-reading of the Mahabharata can provide a perspective that humans must dare to bear their faults instead of running and hiding as told in the Book of Genesis.